El Cauca; la mesoeconomía del oro y la retroactividad de la dependencia: anotaciones sobre coyuntura y desequilibrio territorial. (2013)
Despite the increase in the price of raw materials and the goodness of the projections for the Colombian economy, there are still unclear territorial changes that are trying to reach the height of national macroeconomic successes within gold mining. The aim of this paper is therefore placing in context the space-redistributive implications of this growth pattern in the department of Cauca, highlighting the effects both on sectorial economic composition and the geographical displacement of mining activity.